2022
DOI: 10.1063/5.0096236
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: “Phase behavior of binary hard-sphere mixtures: Free volume theory including reservoir hard-core interactions” [J. Chem. Phys. 154, 074902 (2021)]

Abstract: In this erratum we identify two corrections to our paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…For binary HS mixtures, it has been shown that FF coexistence is metastable for all size ratios. 15 The results in Fig. 3 reveal that FF is predicted to become stable for sufficiently large g. Therefore, it is expected that a certain asphericity is required to stabilize a FF demixing region.…”
Section: Stability Regions Of Fluid-fluid Coexistencementioning
confidence: 85%
See 3 more Smart Citations
“…For binary HS mixtures, it has been shown that FF coexistence is metastable for all size ratios. 15 The results in Fig. 3 reveal that FF is predicted to become stable for sufficiently large g. Therefore, it is expected that a certain asphericity is required to stabilize a FF demixing region.…”
Section: Stability Regions Of Fluid-fluid Coexistencementioning
confidence: 85%
“…In contrast to original FVT predictions, the new FVT method predicts a critical aspect ratio g* below which fluid-fluid (FF) coexistence is metastable with respect to fluid-solid coexistence. This critical aspect ratio is expected because it has been shown that FF coexistence is metastable in binary hard-sphere mixtures for all size ratios 15 and HSC particles reduce to spheres in the limit of g -1. Moreover, FVT predicts that for a certain aspect ratio, there is not only a lower critical size ratio x* E 0.6 below which FF coexistence becomes metastable, but also an upper critical size ratio x* above which FF coexistence is metastable.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations